Analysis of the Effectiveness and Environmental Friendliness of Bottom Hand Line Fishing on the Datoe, Batavier, and Ender Coral Reefs in the Waters of Maas Island, Tual City, Maluku Province - serang, Abu samad; Lambiombir, Enos; Rahantan , Ali; Almohdar , Erna (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
This study aims to analyze the effectiveness and environmental friendliness of bottom hand lines used by fishers around the coral reefs of Datoe, Batavier, and Ender. Labetawi Village was selected as the research site because most of its fishers actively use this gear traditionally and apply selective fishing practices that have the potential to serve as a model for environmentally friendly fisheries in the Tual region. This study analyzes five key parameters: catch efficiency, bycatch-to-target ratio (B/T Ratio), Catch Per Unit Effort (CPUE), gear selectivity, and environmental friendliness. The results show high catch efficiency (76–77%), peaking in July–August at 77.34%, while bycatch remains low (22.66–24.13%). The B/T Ratio values are consistently low and stable, indicating good gear selectivity. The CPUE of target fish was consistently higher than that of non-target fish, although a declining trend was observed from April to September, likely due to fishing pressure and habitat degradation. Bottom hand lines also demonstrated high selectivity, with 79.23% of the catch consisting of target species. Based on nine ecological assessment criteria, a total environmental friendliness score of 33.6 categorizes this gear as environmentally friendly. Thus, bottom hand lines are considered effective and selective in catching target species with minimal ecological impact. Their use is strongly recommended as part of an ecosystem-based fisheries management strategy, with the fishing practices of Labetawi Village serving as an example of efficient, selective, and sustainable traditional fisheries.